Keupayaan Pekerja Mahir dalam Penyerapan Teknologi Baharu di dalam Pembinaan Lebuhraya Pan Borneo Sabah. - Abd Malik, Nur Fathin Munirah; Omar, Roshartini; Mohamed, Sulzakimin; Masrom, Md Asrul Nasid (Research in Management of Technology and Business, 2021)
The construction industry is one of the industries that has undergone a sustainable revolution driven by technology and innovation. Capability technology is the ability of an organization to use technological resources to produce a wide range of products and services. However, there are questions about the ability of skilled workers especially local workers to absorb new technologies transferred into the infrastructure industry. Therefore, this study aims to examine the ability of construction professionals to use technology in construction, identify the types of technologies and challenges that exist in adapting new technologies during the construction of the Pan Borneo Highway. The research was conducted using a semi-structured interview with employees of the Sabah Public Works Department and three Bumiputera contractor companies involved in the construction of the Pan Borneo highway, Sabah. Thus, this measurement can be used as a guide to measure the ability of skilled workers in using technology in the ongoing Pan Borneo highway construction project. To achieve the objectives of the study qualitative methods have been used to collect data from respondents using interview methods. Researchers have used the WhatsApp, Google Form, Google Meet and Email applications as the country is currently experiencing a Covid-19 pandemic that restricts travel across the district where it has restricted researchers from conducting face-to-face interviews to targeted respondents. A total of 5 respondents who have responded to the study interview questions. The data found that the type of technology used by the majority of contractors is software technology such as HIM, PIM and Autodesk. This research also found that respondents’ agreement on the challenges of commitment between teams, allocation and finance, lack of experience is at a high level. While the steps that can be taken by the respondents are to enhance the sharing and communication of knowledge in the organization, intensive from companies and governments, experienced workforce and a conducive organizational cultural environment. In conclusion, with this study, it is hoped that industry players, especially contractors, can benefit in enhancing the ability of skilled workers to absorb technology and expertise in a future project.